Opening the "black box": Factors affecting women's journey to top management positions : a framework applied to Chile - Katherina Kuschel; Erica Salvaj (Administrative Sciences, 2018)
The issue of women's participation in top management and boardroom positions has received increasing attention in the academic literature and the press. However, the pace of advancement for women managers and directors continues to be slow and uneven. The novel framework of this study organizes the factors at the individual, organizational and public policy level that affect both career persistence and the advancement of women in top management positions; namely, factors affecting (1) career persistence (staying at the organization) and (2) career advancement or mobility (getting promoted within the organization). In the study location, Chile, only 32 percent of women "persist", or have a career without interruptions, mainly due to issues with work-family integration and organizational environments with opaque and challenging working conditions. Women who "advanced" in their professional careers represent 30 percent of high management positions in the public sector and 18 percent in the private sector. Only 3 percent of general managers in Chile are women. Women in Chile have limited access and are still not integrated into business power networks. Our findings will enlighten business leaders and public policy-makers interested in designing organizations that retain and promote talented women in top positions.
Keywords: 350; gender; leadership; women in top management; career management; Chile